Prognostic gene expression and microRNA profiling signatures and genetic alterations in primary testicular diffuse large B-cell lymphoma - Wenyu Shi; Zijun Y. Xu-Monette; Youchao Jia; Alexandar Tzankov; Heounjeong Go; Ling Li; Maurilio Ponzoni; Yafei Wang; Qiongli Zhai; Anamarija M. Perry; Shi Wang; Xiaoxiao Wang; et al. (Blood Cancer Journal)
Abstract Primary testicular (PT) diffuse large B-cell lymphoma (DLBCL) is a rare and aggressive lymphoma with distinct clinical and molecular characteristics. To identify prognostic biomarkers in PT-DLBCL, in this study we analyzed DNA and RNA samples of PT-DLBCL tumors from 206 patients using next-generation sequencing platforms and assays. Genetic alteration analysis found that multiple chromosomal copy number variations (CNVs), TP53 transcript mutations with high variant allele frequency, and MCD subtype had significantly adverse prognostic effects, whereas elevated microsatellite instability had a significantly favorable prognostic effect in PT-DLBCL. Targeted RNA-seq analysis identified a PTL gene expression signature by comparing PT-DLBCL with systemic DLBCL and revealed the heterogeneity within PT-DLBCL by unsupervised clustering, which classified PT-DLBCLs into a testicular lymphoma tumor (TLT) subtype and a microenvironment (ME) subtype. The TLT subtype featured upregulation of genes functioning in DNA damage response, DNA repair, chromatin remodeling, the cell cycle, and the nucleus, and was associated with significantly poorer patient survival and higher frequencies of MYD88 mutations, multiple CNVs, MCD subtype, bulk tumors, and elderly patients in the PT-DLBCL cohort. In contrast, the ME subtype distinctively featured upregulation of various signaling pathway genes involving the tumor microenvironment and downregulation of BTK and B-cell receptor signaling genes, and was associated with significantly better clinical outcome than the TLT subtype of PT-DLBCL independently of CNVs, MCD and MYD88 mutation and than systemic DLBCL. Moreover, genomic microRNA profiling analysis identified a PTL microRNA signature significantly differentially expressed between PT-DLBCL and systemic DLBCL patients and within the PT-DLBCL cohort, and PT-DLBCL patients with higher expression of 16 PTL microRNAs (14 are testicular tissue-specific) had significantly better survival. In summary, this study revealed the molecular heterogeneity in genetic abnormalities and expression profiles of coding genes and microRNAs within the PT-DLBCL entity, and identified significant prognostic biomarkers and PTL signatures.